An exploration of HIV/AIDS-related knowledge, attitudes and risky sexual behaviour of first-year psychology students at the University of the Western Cape - Fennie, Thelma (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.